Association of Khat chewing, smoking, age and sex with periodontal status among Yemeni adults - Al-hajj, Wadhah; Hwaiti, Hisham; Shamala, Anas; Al-Azazi, Hamza; Alwesabi, Mohammed (Brazilian Dental Science, 2020)
Objective: Periodontal diseases are very common dental disease. Many risk factors may play significant role in the periodontal disease initiation and progression. This study was performed to evaluate the effects of khat chewing, smoking, age and gender on periodontal status among Yemeni adults. Material and Methods: This cross-sectional study was performed on 1231 patients attending the outpatient dental polyclinics of University of Science and Technology during the academic years 2017/2018.. All completed sheets were collected throughout the year by the supervisors. Data cleaning, descriptive statistics, and inferential statistics were then performed. Results: Khat chewers were more frequent than non-chewers counterparts (60.7% vs. 39.3%). The prevalence of smoking was 25.5% (297 patients). Study results indicated that periodontitis is more associated with female gender and  participants aged more than 35 years old. Results also showed that female and age older participants aged more than 35 years were significantly associated with gingival recession. Mean number of the teeth with gingival recession in male patients were higher than in females. Male gender and patients aged more than 35 years old were significantly associated with furcation involvement. Conclusion: The present study has shown females gender and age older than 35 seem to be risk factors of periodontal diseases. Males has more teeth affected by gingival recession and more furcation involvement.KeywordsPeriodontal disease; Khat chewing; Smoking; Yemen; Risk factors.